The persistence and rise of master planning in urban Africa: transnational circuits and local ambitions - Harrison, Philip; Croese, Sylvia (Routledge, 2022)
Master plans have long been criticized by critical planners who have argued in favour of more strategic, collaborative and relational forms of spatial planning that can more adequately respond to local needs and realities, especially in the context of the global South. Rather than critiquing master planning, this paper seeks to interrogate its recent rise in urban Africa. Building on a review of international planning trajectories, the paper seeks to challenge dominant narratives in the Western literature around the rise and decline of master planning. Planning experiences from across the African continent illustrate how master planning was a limited practice under colonialism and emerged more strongly in early post-colonial years, while persisting through a quiet period of planning and proliferating in recent times. By exploring the diversity in the influences and approaches to master planning for new and existing cities in Africa over time, the paper positions master planning as the product of a complex array of transnational circuits and multiple local actors and ambitions which intersect across different scales. The study of master planning should therefore be considered as an important entry point into understanding and rethinking the contemporary politics of urban planning, implementation, and development in Africa.
Keywords: Master planning || urban development || African cities || urban planning history || new cities || colonial urban planning || postcolonial urban planning || strategic planning